Daya Cipta Bunyi Onomatope sebagai Penggerak Narasi dalam Film Les Voisins De Mes Voisins Sont Mes Voisins - Fika, Ignacia Fauziah; Mutiarsih, Yuliarti; Amalia, Farida (Lingua Susastra, 2025)
This study aims to analyze onomatopoeia in the French animated film Les Voisins de Mes Voisins sont Mes Voisins, focusing on the forms, structures, and functions of onomatopoeia in supporting the narrative. Given that most onomatopoeia studies concentrate on static media, such as comics or literature, this research introduces novelty by examining onomatopoeia within the dynamic audiovisual context of animated film. The study utilizes the onomatopoeia theory proposed by Enckell and Rézeau (2003) and applies a descriptive qualitative methodology using observation and recording techniques. The findings indicate that onomatopoeia can be classified based on the origin and type of sound, possesses three interrelated structural components, and functions significantly to reinforce atmosphere, clarify actions, and convey non-verbal messages. Theoretically, these findings contribute significantly to the fields of audiovisual and linguistics. Specifically, this research explicates the mechanism of onomatopoeia's interaction with visual narration to construct meaning, thereby expanding the understanding of onomatopoeia as an essential tool for strengthening the cinematic atmosphere and emphasizing non-verbal action/emotion within French animated film.